Rancang Bangun Shuttlecock Balancing Tester dengan menggunakan Cooling Fan 120 mm - Nur Aidi Ariyanto; Andre Budhi Hendrawan (Infotekmesin, 2024)
Badminton is a popular sport in the world, especially in countries such as Indonesia, Malaysia, China and many European countries. One of the important elements in badminton is the shuttlecock, which is used as a game ball. The shape density of feather shuttlecocks or synthetic shuttlecocks also affects the movement of the shuttlecock and produces different drag force values. Several methods can be used to test the balance of a shuttlecock, such as a method of throwing it vertically, the method of hitting it manually or using a throwing machine. Both methods show the movement of the shuttlecock directly so that it can be seen whether its movement is balanced or unbalanced, but this method requires a fairly large area. A simpler method is to use a shuttlecock balancing tester (SBT), but the current equipment is noisy and has quite large dimensions so it is not practical. This research aims to develop an existing SBT with less noise, smaller sizes, and more practicality by using a 120 mm cooling fan. The study was carried out to determine the required air flow speed and the correct size of the honeycomb hole. The results of the research show that the airflow speed required in the SBT so that the shuttlecock lifts per floats and rotates stably is 5.0 m/s using a honeycomb hole with a diameter of 6 mm and 4.6 m/s using a honeycomb hole with a diameter of 8 mm . Using 8 mm honeycomb produces air flow with a greater lifting force than using 6 mm honeycomb.